2011
DOI: 10.1101/gad.2005511
|View full text |Cite
|
Sign up to set email alerts
|

Regulating RNA polymerase pausing and transcription elongation in embryonic stem cells

Abstract: Transitions between pluripotent stem cells and differentiated cells are executed by key transcription regulators. Comparative measurements of RNA polymerase distribution over the genome's primary transcription units in different cell states can identify the genes and steps in the transcription cycle that are regulated during such transitions. To identify the complete transcriptional profiles of RNA polymerases with high sensitivity and resolution, as well as the critical regulated steps upon which regulatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
305
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(341 citation statements)
references
References 55 publications
29
305
2
1
Order By: Relevance
“…Aggregate patterns of transcription profiles showed enrichment of reads within 1.5 kb of TSSs genome-wide (Fig. S1B, Right), consistent with previously published GRO-seq results obtained in other cell types (30,31). To perform HTGTS for DSB identification, we used a Cas9:sgRNAbased approach to introduce HTGTS bait DSBs into primary NSPCs isolated from Xrcc4 −/− p53 −/− mice, as previously described (4).…”
Section: Dsbs and Translocations Are Enriched Around Active Tsss In Nsupporting
confidence: 57%
See 1 more Smart Citation
“…Aggregate patterns of transcription profiles showed enrichment of reads within 1.5 kb of TSSs genome-wide (Fig. S1B, Right), consistent with previously published GRO-seq results obtained in other cell types (30,31). To perform HTGTS for DSB identification, we used a Cas9:sgRNAbased approach to introduce HTGTS bait DSBs into primary NSPCs isolated from Xrcc4 −/− p53 −/− mice, as previously described (4).…”
Section: Dsbs and Translocations Are Enriched Around Active Tsss In Nsupporting
confidence: 57%
“…To assess whether transcription-associated DSBs occur and form translocations in NSPCs, we first identified actively transcribed genes by performing GRO-seq (8,30,31) in Xrcc4 −/− p53 −/− NSPCs. In these analyses, a Pearson correlation coefficient analysis showed high reproducibility among three independent experiments (Fig.…”
Section: Dsbs and Translocations Are Enriched Around Active Tsss In Nmentioning
confidence: 99%
“…Instead, the majority of promoters are marked by H3K4me3, regardless of the gene expression status [63,64]. Although the presence of both H3K4me3 and Pol II at promoter is an indication of transcription allowance [63,64], productive transcription relies on the rate-limiting step of RNA Pol II releasing from the promoter [63,65,66]. The inactive state of some H3K4me3-marked genes can also be attributed to the coexistence of repressive modifications, such as H3K27me3 (see below).…”
Section: H3k4 Methylationmentioning
confidence: 99%
“…The kinase activity of P-TEFb Drosophila cells revealed that loss of NELF-mediated pausing reduced RNA Pol II promoter occupancy at most, but not all, promoters, 2 globally implicating NELF in inhibition of early elongation. The high sensitivity of the global runon-sequencing (GRO-seq) technique, 51 allowed the determination that even active genes undergo transient pausing of RNA Pol II, 47,52 suggesting that NELF-mediated pausing may be a general feature of the transcription mechanism. Furthermore, these studies suggest that the efficiency of pause release, rather than the establishment of pausing, plays a major role in determining gene expression levels.…”
Section: Sp3 Regulates the Balance Of Kinase And Phosphatase Activitimentioning
confidence: 99%
“…47 Following initiation, RNA Pol II falls under the control of negative elongation factors, including DRB (5,6-ichlorobenzimidazole riboside) sensitivity-inducing factor (DSIF) and the negative elongation factor complex (NELF). NELF is the major factor associated with the early pausing of RNA Pol II.…”
Section: Sp3 Promotes Occupancy Of the Nelf Complexmentioning
confidence: 99%